Altas habilidades/superdotação: conhecimento científico e informação midiática - Mani, Eliane Morais de Jesus (Universidade Federal de São Carlos, 2019)
In Brazil, public policies for Special Education offer guarantees for identifying and serving students with high abilities/giftedness. However, there is a static situation of invisibility of these students in the educational scenario, due to the lack of knowledge on the subject, observed in the inexpressiveness of the minimum enrollment data for these students, in addition to the low scientific production in this field. Moreover, the media is an important communication vehicle to transmit, as well as to information, socially constructed knowledge, especially that which is based on scientific evidence, since the media has high relevance for the formation of opinion and the adoption of values, concepts and concepts that reflect and influence the citizen profese. In this study, the aim was to investigate and analyze the media representations of high abilities/giftedness in six vehicles, two on television and four in the written press, in the years 2008 to 2018. The specific objectives were: to verify the incidence of theses and dissertations that address the dissemination of high skills/giftedness in the media; and, identify and categorize the reports of the Brazilian communication vehicles signaled about high abilities/giftedness. For that, a documental and descriptive research was developed. The searched media were: television media – Rede Globo and Record TV; written media – newspapers: Estado de São Paulo (Estadão) and Folha de São Paulo – magazines: Veja and Isto é. The results brought a total of 143 reports, including written and televised publications, published over a period of 10 years, on the theme of high abilities/giftedness. The categories on the themes that stood out the most in these publications were identification and service. An important factor found was the presence of myths in the reports, especially referring to the idea of genius associated with high abilities/giftedness. Thus, it was possible to conclude that despite the advances in the legal sphere regarding the inclusive educational process in the country, the media vehicles have not contributed as expected with the dissemination of scientific knowledge in relation to the area of high abilities/giftedness, so that it is possible to break, mainly with the lack of knowledge, myths and inattention present in the social and educational context, arising from common sense.
High skills/giftedness: scientific knowledge and media information
Keywords: Educação especial; Altas habilidades/superdotação; Mídia; High skills/guiftness; Special education; Media; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS